Smart fan - Leong, Hin Chee. (2008)
This thesis consist of 2 parts. Involves in altering the oscillation sweep angle to improve the efficiency of electric fan. The conceptual and detail design of a Smart Fan that is able to find human users and oscillates itself between the targets.